2008
DOI: 10.1038/jcbfm.2008.92
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD34-Positive Cells Have Prognostic Value for Neurologic Function in Patients with past Cerebral Infarction

Abstract: Increasing evidence points to a role for circulating endothelial progenitors, including populations of CD34-positive (CD34 + ) cells present in peripheral blood, in vascular homeostasis and neovascularization. In this report, circulating CD34 + cells in individuals with a history of cerebral infarction were correlated with changes in neurologic function over a period of 1 year. Patients with decreased levels of CD34 + cells displayed significant worsening in neurologic function, evaluated by the Barthel Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Further studies are needed to investigate exactly the prognostic value of this difference of progenitor cells among patients with moderate to severe AD. The potential clinical relevance of these findings has recently been demonstrated by Taguchi and colleagues [27], showing that circulating CD34 + HSCs have prognostic value for neurologic function in patients with past cerebral infarction. Hematopoietic stem and progenitor cells could take part in tissue healing processes of the brain through several mechanisms.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Further studies are needed to investigate exactly the prognostic value of this difference of progenitor cells among patients with moderate to severe AD. The potential clinical relevance of these findings has recently been demonstrated by Taguchi and colleagues [27], showing that circulating CD34 + HSCs have prognostic value for neurologic function in patients with past cerebral infarction. Hematopoietic stem and progenitor cells could take part in tissue healing processes of the brain through several mechanisms.…”
Section: Discussionmentioning
confidence: 76%
“…As limiting factors of this study, there is given no information about age, gender distribution, MMSE scores, and treatment of the included patients and the time point of blood collection, which may have influenced the results. In contrast, Taguchi et al [27] showed a significant decrease of circulating CD34 + HSCs only in patients with vascular-type cognitive impairment, but not in AD patients with different severity of dementia. However, there is no information about MMSE scores and the time point of blood collection, an imbalance regarding the use of NSAIDs between the patients with vascular dementia (58%) and AD (4%), and a small sample size, which may have biased the results from this study.…”
Section: Discussionmentioning
confidence: 84%
“…It is entirely possible that some HSC integrate into the vasculature and others transdifferentiate into neurons. However, the majority of studies focus either on vascular beds (Taguchi et al, 2009) or neuronal regeneration (Garzon-muvdi et al, 2009) rather than both.…”
Section: Are Hsc a Viable Avenue For Stroke Therapy?mentioning
confidence: 99%
“…However, the field of Hematopoietic stem cell (HSC) research in stroke is not barren, as a small volume of literature has recently emerged. HSC have recently been shown to mobilize to the peripheral circulation from bone marrow in response to stroke (Hennemann et al, 2008), and increasing circulating HSC levels correlate with improved neurological function following stroke, suggesting a potentially critical role for HSC in limiting stroke injury and/or facilitating stroke recovery (Yip et al, 2008;Taguchi et al, 2009). Moreover, post-ischemic intravascular administration of exogenous HSC has recently been shown to ameliorate ischemic stroke in mice (Schwarting et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation